2017
DOI: 10.1038/s41598-017-16863-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of porous knitted titanium for replacement of intervertebral disc nucleus pulposus

Abstract: Effective restoration of human intervertebral disc degeneration is challenged by numerous limitations of the currently available spinal fusion and arthroplasty treatment strategies. Consequently, use of artificial biomaterial implant is gaining attention as a potential therapeutic strategy. Our study is aimed at investigating and characterizing a novel knitted titanium (Ti6Al4V) implant for the replacement of nucleus pulposus to treat early stages of chronic intervertebral disc degeneration. Specific knitted g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The topography changes of titanium surfaces were not observed under high magnifications above ×30,000 on untreated discs fabricated with different laser parameters. Tendulkar et al [ 58 ] reported intervertebral disc made from titanium wire with Ra around 15 µm and contact angle almost 90° which remained almost unchanged after electro-polishing, while Ra parameter decreased around 3 times. In our study the 4–6-fold decrease in the surface energy of the titanium discs with the simultaneous lack of improvement of parameter Ra resulted from thermal treatments in 600 °C for 1 h. Furthermore annealing changed the contact angle to more hydrophilic values equal 90° and 72° after treatment in vacuum and oxygen atmosphere, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The topography changes of titanium surfaces were not observed under high magnifications above ×30,000 on untreated discs fabricated with different laser parameters. Tendulkar et al [ 58 ] reported intervertebral disc made from titanium wire with Ra around 15 µm and contact angle almost 90° which remained almost unchanged after electro-polishing, while Ra parameter decreased around 3 times. In our study the 4–6-fold decrease in the surface energy of the titanium discs with the simultaneous lack of improvement of parameter Ra resulted from thermal treatments in 600 °C for 1 h. Furthermore annealing changed the contact angle to more hydrophilic values equal 90° and 72° after treatment in vacuum and oxygen atmosphere, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, a high number of MSC lines that display specific characteristics and differentiation capabilities have been generated and are valuable tools as part of models of disease and tissue repairing strategies. Different MSC lines have been employed for testing [17,[20][21][22][23][24][25] or producing [26,27] engineered scaffolds for skeletal applications, and for both investigating the MSC differentiation process [28][29][30][31][32][33][34] and finding new ways to improve it [35][36][37][38][39]. Additionally, these cell lines have also been used for analyzing functional makers [19,40] or even for exploring their roles in different diseases, such as osteoarthritis [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatibility is a fundamental prerequisite for any biomaterial to be used in tissue engineering. Thus, a knitted titanium scaffold, which showed in our previous studies a high biocompatibility, was used as an example for the 3D cultivation of cells for potential application in IVD treatment [23]. SCP1 cells and primary human chondrocytes were seeded on these biocompatible knitted titanium scaffolds and the transfectability of these cells was analyzed using lipoplexes-containing Lipofectamine 2000 and 1 µg eGFP mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, in this study, we analyzed a combined approach of synthetic Link N mRNA delivery together with knitted titanium scaffold as a promising strategy for improving and supporting the reparative processes for the treatment of joint tissues. Previously, our group demonstrated that knitted titanium scaffold, which was aimed for IVD nucleus pulposus replacement, supports cell attachment, growth of human primary chondrocytes as well as SCP1 cells in vitro [23]. Importantly, the 3D architecture of the porous knitted titanium scaffold is expected to play a role in maintaining space, which is necessary for tissue integration upon implantation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation